Fear of missing out, price sensitivity, and customer online impulse buying: The role of scarcity cues - Yusuf Suhardi; Ali Akhmadi; Arya Darmawan (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
This research aims to examine the effect of fear of missing out (FoMO) on impulse buying and the mediation effect of price sensitivity, and the moderator effect of scarcity cues in these relations. Three hundred and eighty-four students from two universities in Jakarta were involved in the study by completing a two-phase online questionnaire. Moderation and mediation procedure (MODMED) was applied to test the hypothesis with Macro Process 4.0. The empirical findings of this study demonstrate that fear of missing is negatively related to price sensitivity and positively related to impulse buying. Fear of missing out has also been confirmed to affect impulse buying through price sensitivity indirectly. Furthermore, according to expectations, scarcity cues were also verified to strengthen the effect of fear of missing out and price sensitivity on impulse buying.